Running and addiction: precipitated withdrawal in a rat model of activity-based anorexia - Kanarek, Robin B; D'Anci, Kristen E; Jurdak, Nicole; Mathes, Wendy Foulds (Behavioral neuroscience, 2009)
Exercise improves cardiovascular health, strengthens muscles and bones, stimulates neuroplasticity, and promotes feelings of well-being. However, when taken to extremes, exercise can develop into an addictive-like behavior. To assess the addictive potential of exercise, withdrawal symptoms following injections of 1.0 mg/kg naloxone were compared in active and inactive male and female rats. Active and inactive rats were given food for 1 hr or 24 hr/day. Additionally, a group of inactive rats was pair-fed the amount of food consumed on the previous day by food-restricted active rats. Rats fed for 1 hr/day decreased food intake and lost weight. Additionally, food-restricted active rats increased wheel running. There was a direct relationship between the intensity of running and the severity of withdrawal symptoms. Active food-restricted rats displayed the most withdrawal symptoms, followed by active rats given 24-hr access to food. Only minimal withdrawal symptoms were observed in inactive rats. These findings support the hypothesis that exercise-induced increases in endogenous opioid peptides act in a manner similar to chronic administration of opiate drugs.